Analisis Potensi Pengembangan Program Z-AUTO BAZNAS Banyumas Dalam Mendorong Kemandirian Ekonomi Mustahik - QORRI AINA ANIDA PUTRI; ARYA HANS PUTRA; DWI YAN FAUZI RAKHMAN; MAHARDHIKA CIPTA RAHARJA (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the potential of the Z-Auto program by BAZNAS Banyumas Regency in supporting the economic independence of mustahik through the utilization of productive zakat in the automotive sector. The Z-Auto program is a form of economic empowerment implemented through automotive skills training, provision of business equipment assistance, and business mentoring for mustahik. This research is motivated by the increasing number of motor vehicles in Banyumas Regency, which has led to a higher public demand for vehicle repair and maintenance services, thereby creating promising business opportunities in the motorcycle workshop sector. This study employs a qualitative descriptive approach using the library research method. The research data were obtained from various secondary sources, including scientific journals, books, official reports, and statistical data relevant to the research topic. Data analysis techniques were conducted through qualitative descriptive analysis and SWOT analysis to identify internal and external factors influencing the potential of the Z-Auto program. The findings indicate that the Z-Auto program has considerable potential in enhancing the economic independence of mustahik. This potential is supported by broad market opportunities in the automotive sector, skills training, business equipment assistance, and business mentoring that help mustahik develop independent and sustainable businesses. However, the program still faces several challenges, such as limited managerial capabilities of mustahik, business competition, and the continuous development of automotive technology. Therefore, the Z-Auto program has the potential to become a productive zakat-based economic empowerment model capable of improving the welfare and economic independence of mustahik sustainably.